mathematical modeling, training, knowledge, skills, student skills, biomedical processes and systems, optimization, application. - Tuychiev, Laziz; Marasulov, A.F.; Bazarbaev, Muratali; Ermetov, Erkinboy (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
An approach to teaching mathematical modeling is proposed, focused on the improved formation of students’ knowledge, skills, which is based on modeling and research of complex biomedical processes and systems, their optimization, application of various types and methods of modeling in specific conditions.